The Modified Nutrition Risk in Critically III (mNUTRIC) Score associated with Clinical Outcome and Length of Stay in Intensive Care Unit (ICU) Patients - Galuh Dwi Anjani; Mirza Junando; Rasmi Zakiah Oktarlina; Rani Himayani; Nurma Suri (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2025)
Background: Malnutrition is a common issue in hospital settings, particularly in the ICU and among elderly patients. Objective: This study aimed to analyze the nutritional characteristics of ICU patients and their association with clinical outcomes and length of stay. Methods: This prospective observational study was conducted in the ICU of Dr. H. Abdul Moeloek Hospital, Lampung Province, from December 2023 to February 2024. Patients hospitalized during this period were the study population, with total sampling used to collect data. The mNUTRIC score was employed to assess nutritional status. Bivariate analysis using chi-square was conducted to analyze the association between mNUTRIC scores and patient outcomes, as well as length of stay. Results: The majority of patients were elderly aged 50-75 years (45%) and female (95%). A significant portion (68.3%) had an abnormal body mass index (underweight, overweight, or obese). Additionally, 91.7% had comorbidities, and most stayed in the ICU for more than three days, with 51.7% having extended stays. Furthermore, 48.3% passed away during hospitalization. The study found that 51.7% of patients were at high nutritional risk, while 48.3% were at low risk. Bivariate analysis revealed a significant correlation between mNUTRIC score and clinical outcomes, including length of stay (p<0.05). Conclusion: This study concludes that ICU patients often have an abnormal nutritional risk, either high or low, based on mNUTRIC scores. Furthermore, mNUTRIC scores are correlated with clinical outcomes and length of stay.